Classifying Lean Production: A Review of Empirical Research - Marshall, David A. (International Journal of Supply Chain Management, 2015)
Lean production has been studied extensively during the past few decades.  Many authors agree that Western production techniques are outdated and that there is a significant shift towards the “Lean” production philosophy.  The purpose of this paper is to review and classify the lean production empirical research, identify well-traveled paths, and offer suggestions for future research.  Articles were collected from the premier refereed journals in the fields of Supply Chain and Operations Management.  Classification of the articles utilizing a “SPOT” model based on four fundamental lean production principles is presented in the paper.  A majority of the articles included in this review concentrate on an operations or elimination of waste element.  Future research paths, including “Sustainable” lean production are discussed.